Meningococcal Neonatal Purulent Conjunctivitis/Sepsis and Asymptomatic Carriage of N. meningitidis in Mother’s Vagina and Both Parents’ Nasopharynx - Enrique Chacon-Cruz; Jorge Arturo Alvelais-Palacios; Jaime Alfonso Rodriguez-Valencia; Erika Zoe Lopatynsky-Reyes; Maria Luisa Volker-Soberanes; Rosa Maria Rivas-Landeros (Case Reports in Infectious Diseases)
Neonatal conjunctivitis is usually associated with vagina’s infection by Chlamydia sp., N. gonorrhoeae, and/or other bacteria during delivery. Meningococcal neonatal conjunctivitis is an extremely rare disease. We report a case of neonatal meningococcal sepsis/conjunctivitis and asymptomatic carriage of N. meningitidis from both parents (vagina and nasopharynx). As part of our active surveillance for meningococcal disease at the Tijuana General Hospital (TGH), Mexico, we identified a 3-day-old newborn with meningococcal conjunctivitis and sepsis. The patient had a one-day history of conjunctivitis and poor feeding. Clinical examination confirmed profuse purulent conjunctival discharge, as well as clinical signs and laboratory findings suggestive of bacteraemia. Gram stain from conjunctival exudate revealed intracellular Gram negative diplococci; we presumed the baby had gonorrheal conjunctivitis; however, serogroup Y, N. meningitidis was isolated both from conjunctival exudate and blood. Additionally, isolation of serogroup Y, N. meningitidis was obtained from mother’s vagina and both parents’ nasopharynx. The baby was treated with 7 days of IV ceftriaxone and discharged with no sequelae.